The role of CSR in Cotton On’s KwaMashu upliftment initiative on Consumer Loyalty in Pretoria - Loganathan, Tanya Marie (The IIE, 2020)
In this study, the researcher sets out to understand the importance of Corporate Social Responsibility and investigate how consumer loyalty impacts the Cotton On Foundation initiative. This plays a vital role in making a difference in the KwaMashu Community by providing quality education through skills development to the youth, by eliminating the circle of poverty. For this research study, a qualitative approach was used to obtain a deeper understanding of the differential opinions of consumer loyalty from the consumers within the Cotton On Group. Three semi-structured interviews were conducted to gather data from the participants to get a clear understanding of the various perspectives QDA Miner Lite, a qualitative analysis program, was used to transcribe the responses from the results reflected that the CSR initiative by Cotton On, creates and develops consumer loyalty as all respondents indicated. They were motivated to purchase more Cotton On Foundation items, more frequently, as a means of giving back to the less fortunate residing in the rural KwaMashu Community. Overall, a better understanding was gained as to why Cotton On consumers chose to remain loyal towards the CSR initiative.
Keywords: Corporate Social Responsibility (CSR); Consumer loyalty; Non-profit organisation (NPO); Initiatives; KwaMashu Community; Skills development; Empowering youth through quality education